Environmental tax reform and income distribution with imperfect heterogeneous labour markets - Aubert, Diane; Chiroleu-Assouline, Mireille (Munich, 2017)
"This paper investigates the distributional and efficiency consequences of an environmental tax reform, when the revenue from the green tax is recycled by varying labor tax rates. We build a general equilibrium model with imperfect heterogeneous labor markets, pollution consumption externalities, and non-homothetic preferences (Stone-Geary utility). We show that in the case where the reform appears to be regressive, the gains from the double dividend can be made Pareto improving by using a redistributive non-linear income tax if redistribution is initially not too large. Moreover, the increase of progressivity acts on unemployment and can moderate the trade-off between equity and efficiency. We finally provide numerical illustrations for three European countries featuring different labor market behaviors. We show that a double dividend may be obtained without worsening the initial inequalities if the green tax revenues are redistributed with a progressivity index lower for UK than for France and Germany."